Memahami Imago Dei Sebagai Potensi Ilahi dalam Pelayanan Kristiani - Marcellius Lumintang; Binsar Mangaratua Hutasoit; Clartje S.E. Awulle (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2017)
Abstract: Golden moment is a term that refers to someone’s or church’s achievement and glory. It is not the utopian concept, yet a conviction and expectation based on God’s promise for His people. Some factors are required to achieve the golden moment, one of them is a Golden Seed. Imago Dei is a golden seed which gives an opportunity to the golden moment. This article has a purpose to gice a biblical view of imago Dei which is inside of every human. This article used a bible exposition method on Genesis 1:26, which explained that human was created in a frame of Imago Dei. The conclusion is, that imago Dei is a golden seed which enables every people has the golden moment. Abstrak: Golden moment merupakan istilah untuk menunjukkan sebuah masa keemasan seseorang atau gereja, seperti masa kejayaan atau pencapaian. Golden moment bukanlah konsep utopis, melainkan sebuah keyakinan dan pengharapan berdasarkan janji Tuhan bagi umat pilihan-Nya. Ada banyak faktor yang dibutuhkan untuk seseorang mencapai golden moment, salah satunya adalah: Golden Seed atau benih emas. Imago Dei merupakan benih emas yang dapat memberikan kesempatan setiap orang mencapai golden moment. Artikel ini bertujuan untuk memberikan pandangan biblikal tentang Imago Dei yang ada pada diri setiap manusia secara hakiki. Metode yang digunakan adalah eksposisi Kejadian 1:26, di mana menjelaskan tentang manusia diciptakan dalam kerangka imago Dei. Kesimpulannya, imago Dei merupakan benih emas yang memungkinkan setiap orang memiliki golden moment.